Penguatan Perilaku Hidup Bersih dan Sehat melalui Sosialisasi Interaktif pada Siswa Sekolah Dasar di Desa Babakan Asem - Nurhikmah, Dentian; Intani, Adela Nur; Arista, Gina Dwi; Lestari, Aprilia Kasih (Universitas Mataram, 2025)
Perilaku Hidup Bersih dan Sehat (PHBS) is an important indicator in improving public health, especially for elementary school-aged children who are in the phase of forming long-term habits. Students' low knowledge of basic health practices, especially in rural areas, is an obstacle to optimal PHBS implementation. This community service activity aims to increase students' knowledge, understanding, and awareness of PHBS through educational outreach at Babakan Asem Elementary School and Neglasari Elementary School. The outreach method used a multimodal learning approach that included interactive lectures, visualizations through PowerPoint and video media, discussions, icebreakers, demonstrations of the seven steps of handwashing, and the